Attitudes of journalists who write about suicide towards guidelines for reporting on suicide and both favourable and unfavourable factors for compliance with the guidelines - Eimontas, Jonas; Gailienė, Danutė (Psichologija, 2014)
Lithuania has one of the highest suicide rates in the world, but the issue hasn’t been properly addressed at the state level. Scientists have demonstrated that the inappropriate media portrayal of suicide can lead to imitative suicidal behavior. Specialists who understood the impact that the media reporting on suicide may cause have set up and started distributing recommendations for reporting on suicide. Recent findings show that the Lithuanian media has not yet developed the practice of responsible reporting on suicide, but there are signs that the situation is slowly improving (Eimontas, 2013). Studies from around the world show that there are several factors that contribute to the way reporters use and appreciate the guideliness for reporting on suicide. The purpose of the present study was to explore the attitudes towards suicide of the Lithuanian journalists who have written most about suicide during the years 2010 and 2011 and to identify both favourable and unfavourable factors for compliance with the guidelines.Methods. After analyzing 721 articles about suicide written in 2010–2011, we identified 50 journalists who covered the topic of suicide most often. The total of 12 reporters had been interviewed. Six of them were selected from those who have written the majority of articles about suicide (which did not conform to the guideliness) during the years 2010 and 2011. Six others were selected from the ones that have reported on suicide many times during the period, but their articles did conform to the guidelines. A thematic analysis was used to examine the data gathered during the interviews.Results. In this study, four out of 12 (33 percent) journalists who have written most often about suicide in 2010–2011 were not aware of the recommendations for reporting on suicide. The thematic analysis of the interviews with journalists has allowed to distinguish at least five factors that help to explain what factors influence whether journalists would use the guidelines when reporting on suicide. These factors are: personal characteristics of a journalist, journalists’ experience with suicide, knowledge about suicide, attitudes towards suicide, as well as guidelines and external influences (such as the editor, or the policy of the editorial office).
Keywords: suicide imitation effect; guidelines for reportinf on suicide; media; suicide; guidelines